2010
DOI: 10.1007/s10545-010-9058-x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term follow‐up of patients with phenylketonuria receiving tetrahydrobiopterin treatment

Abstract: Treatment with tetrahydrobiopterin (BH4), the natural cofactor of phenylalanine hydroxylase (PAH), can reduce blood phenylalanine (Phe) levels in patients with BH4-responsive phenylketonuria (PKU). A number of studies has reported on the short-term BH4 treatment of patients with PKU, but long-term data are lacking. Here, we describe the effects of long-term treatment with BH4 on 16 patients, who showed a >28% reduction in blood Phe following testing for BH4 overload. The mean dose of BH4 was 16 mg/kg body weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 11 publications
3
22
0
1
Order By: Relevance
“…This percentage is similar to that of other studies (Trefz et al 2010). Other authors obtained a far superior rate of response, 62%, (Vernon et al 2010); this may be because the loading test experiments are performed under dietary supplementation with a low-phe food.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This percentage is similar to that of other studies (Trefz et al 2010). Other authors obtained a far superior rate of response, 62%, (Vernon et al 2010); this may be because the loading test experiments are performed under dietary supplementation with a low-phe food.…”
Section: Discussionsupporting
confidence: 89%
“…Although this formulation has been used extensively in experimental studies, it has not been evaluated in formal clinical trials and was not recorded. A newer formulation of BH4 (sapropterin dihydrochloride, Kuvan ® ) for the treatment of PKU that is more stable at room temperature has been available in the USA and Europe (Burnett 2007) Burton et al 2011;Blau et al 2010;Vernon et al 2010;Trefz et al 2010). No serious adverse events with BH4 treatment were reported in medical literature (Belanger-Quintana et al 2005;Nielsen et al 2010); headache, upper respiratory tract infections, and rhinorrhea were the side effects observed in sapropterin-treated patients with PKU in clinical trials (Kuvan Trefz et al 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…with our model, including all patients with blood Phe levels >180 µmol/L, was similar to that reported in a study of 24 patients with PKU that included adolescents with poor dietary control and neonates with HPA (50-54%) [29]. The better response observed in newborns may be because it is easier achieve compliance in infants than in older children.…”
Section: Accepted Manuscriptsupporting
confidence: 72%
“…In 1999, the treatment of PKU patients with tetrahydrobiopterin (BH4), the cofactor of PAH, has been described for the first time [2]. Since then, multiple studies reported on the effect of BH4 in PKU patients with PAH deficiency [3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%